The Effectiveness of Educational Game-Based Fraaction Dominoes in Enhancing Fifth-Grade Students’ Understanding of Fraaction Concepts at MI DDI Manding Polewali Mandar - Junaedi Junaedi; Ayyub Daeng Pananrang; Rivai Makduani; Muh. Aji Saputra; Abdul Wahab; Ridwan Ridwan (Universitas Islam DDI A.G.H Abdurrahman Ambo Dalle, 2026)
This study aims to describe the use of fractional domino cards as a medium and to analyze the improvement in mathematics learning outcomes of fifth-grade students at MI DDI Manding, Polewali Mandar District through the application of this media. This study uses a descriptive qualitative research type with a communication and education approach. Data sources consist of primary and secondary data obtained through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of fractional domino cards as a medium is effective in helping students understand the concept of fractions in a concrete and interactive manner. The application of this media has been proven to improve mathematics learning outcomes, especially in the material on fractional conversion, as indicated by an increase in the average score of students from the sufficient category to good and very good. In addition, the use of fractional domino cards also has a positive impact on the affective and psychomotor aspects of students. In the affective aspect, students show increased courage in expressing opinions, the ability to work together, and an attitude of respect for friends. In the psychomotor aspect, students are more skilled in using media, increasing their thinking speed, calculation accuracy, and the ability to develop learning strategies through games. Thus, fractional domino card media can be an effective learning alternative to improve the quality of mathematics learning, create a fun, interactive learning atmosphere, and be able to develop students' cognitive, affective, and psychomotor abilities in a balanced manner.